Long‐term study of oral treprostinil to treat pulmonary arterial hypertension: dosing, tolerability, and pharmacokinetics. (1st December 2020) - White, R. James; Parikh, Keyur; Allen, Roblee; Feldman, Jeremy; Jerjez‐Sanchez, Carlos; Pan, Lei; Keogh, Anne; Vizza, C. Dario; Shapiro, Shelley; Gordon, Kathryn; Broderick, Meredith; Bartolome, Sonja
Abstract : Oral treprostinil may be an option for low‐ and intermediate‐risk patients with pulmonary arterial hypertension, a rare lung vascular disease. This open‐label extension study collected data on participants who completed previously reported, placebo‐controlled oral treprostinil studies. Eligible participants had completed the prospective parent studies and took increasing doses of oral treprostinil twice daily; some later transitioned to three times daily dosing. Investigators measured 6‐minute walk distance at Month 12 as the sole efficacy measure but collected adverse events throughout the study. A single center measured pharmacokinetics in 13 subjects who changed dosing from twice daily to three times daily. Eight hundred and ninety‐four participants enrolled and 71% completed one year of therapy, with a median total daily dose of 7 mg and a median 6‐minute walk distance increase of 22 m (interquartile range, −14 to 67 m). Subjects achieving higher doses had larger increases in 6‐minute walk distance; 42% of participants completed three years of therapy. Adverse events were typical for prostacyclin class therapy, but prostacyclin‐type adverse events may have been better tolerated with three times daily dosing in 105 participants. In 13 participants transitioned to three times daily dosing with pharmacokinetic measurements before and after, trough drug levels were higher with three times daily dosing. Oral treprostinil is associated with modest but durable, dose‐responsive effects on exercise tolerance for those who remained on therapy at one year in this prospective, uncontrolled study. Three times daily dosing was associated with higher trough levels and better tolerability. The recently completed Freedom‐EV study will provide further insights into the utility of oral treprostinil (https://clinicaltrials.gov/show/NCT01560624 ).